Analysis of Relationship of Breastfeeding Behaviour in Working Mothers and The Incident of Stunting - Dewi Agustin; Lusi Noviyanti; Sisca Pri Andini; Sakinah Agilia (Lembaga Pengembangan Kinerja Dosen, 2024)
Stunting problems often occur in children who lack essential nutrients, especially protein, iron and other nutrients needed for optimal growth. Stunting is not only a physical problem that can be seen from short height, but also has serious long-term impacts on children's development. Exclusive breast milk is a primary need for babies, so it will have an impact on the baby's growth and development if it is not provided adequately. Breast milk that is not given exclusively in the first 6 months of a baby's life will have an impact on the maturation process of the immune system, causing the baby to be susceptible to infections (Wasiah, 2019). Bekasi Regency is an industrial area with more than 3.5 million residents and 44.6% of them are women. A total of 523 461 of them are working women who are in the productive age range of 15-49 years. In this age range, many working women are mothers who have to leave their babies and be cared for by someone else and cannot provide exclusive breast milk. The failure to provide exclusive breastfeeding is the driving force behind many cases of stunting in Indonesia. This research is a quantitative analytical research with a cross sectional approach with the respondents being working mothers who have children under five. P value is 0.021 and OR 8,000, so there is a significant relationship between breastfeeding behavior and the incidence of stunting in the Kedungwaringin Community Health Center Working Area. Working mothers with non-exclusive breastfeeding behavior increase the risk of stunting by 8,000 times compared to mothers who breastfeed exclusively.